Dietary Conjugated Linoleic Acid Supplementation Leads to Downregulation of PPAR Transcription in Broiler Chickens and Reduction of Adipocyte Cellularity - Suriya Kumari Ramiah; Goh Yong Meng; Tan Sheau Wei; Yeap Swee Keong; Mahdi Ebrahimi (PPAR Research)
Conjugated linoleic acids (CLA) act as an important ligand for nuclear receptors in adipogenesis and fat deposition in mammals and avian species. This study aimed to determine whether similar effects are plausible on avian abdominal fat adipocyte size, as well as abdominal adipogenic transcriptional level. CLA was supplemented at different levels, namely, (i) basal diet without CLA (5% palm oil) (CON), (ii) basal diet with 2.5% CLA and 2.5% palm oil (LCLA), and (iii) basal diet with 5% CLA (HCLA).The content of cis-9, trans-11 CLA was between 1.69- and 2.3-fold greater (P<0.05) than that of trans-10, cis-12 CLA in the abdominal fat of the LCLA and HCLA group. The adipogenic capacity of the abdominal fat depot in LCLA and HCLA fed chicken is associated with a decreased proportion of adipose cells and monounsaturated fatty acids (MUFA). The transcriptional level of adipocyte protein (aP2) and peroxisome proliferator-activated receptor gamma (PPARγ) was downregulated by 1.08- to 2.5-fold in CLA supplemented diets, respectively. It was speculated that feeding CLA to broiler chickens reduced adipocyte size and downregulated PPARγ and aP2 that control adipocyte cellularity. Elevation of CLA isomers into their adipose tissue provides a potential CLA-rich source for human consumption.